The relative influence of kick rate and stroke rate on front crawl velocity and metabolic cost - Morris, K.; Osborne, M.; Shephard, M.; Jenkins, D. G.; Skinner, T. L. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The extent to which kick rate influences front crawl velocity and metabolic cost while considering the impact of other biomechanical and individual characteristics on swimming performance is currently unknown. To inform methodology for future physiological and/or talent identification testing sessions, this study aimed to determine the relative importance of biomechanical parameters (stroke and kick rate) and individual characteristics (200-m freestyle personal best, sex and anthropometry) on submaximal front crawl velocity and metabolic cost. Thirty-six national-level swimmers performed two submaximal 200-m front crawl efforts; velocities were equivalent to 64 ± 6% and 77 ± 5% of participants` 200-m personal best velocity. Skinfolds, body mass, oxygen uptake, blood lactate concentration, velocity, stroke rate, kick rate and metabolic cost were measured. Two multiple linear regression analyses were conducted; one with velocity and the other with metabolic cost as the dependent variable. The input variables explained 73.2% of the variance in velocity (p<0.001) and 23.3% of the variance in the metabolic cost (p=0.001). Stroke rate, sum of seven skinfold sites, kick rate, and body mass all contributed to the velocity model, while body mass was the only contributor to the metabolic cost model. Biomechanical and anthropometry parameters explain the vast majority of variance in velocity while the metabolic cost of submaximal swiming appears to be influenced by other factors not considered in the present study. Considering their contributions to velocity, both the stroke and kick rates should be measured and controlled when collecting and interpreting data from physiological testing sessions. Additional parameters (e.g. intra-cyclic velocity fluctuations, index of coordination and kick depth) should be explored in conjunction with stroke and kick rate in future studies to further explain the variance in metabolic cost.